Task-Driven: Does It Effect on Students’ Mathematical Reasoning Skills? - Napitupulu, E Elvis; Minarni, Ani (Advances in Social Sciences Research Journal, 2019)
One of the most difficult task to handle in part of students in learning mathematics is mathematical reasoning. Due to the deficiency, this study attempted to help the students grasp the skill by disseminating a set of learning materials, which had been developed in the previous study and fulfilled the validity, practicality, and effectivity criteria. The learning materials consisted of student book (SB) and student worksheet (SW). The developing of the two devices (SB and SW) intended to improve the students mathematical reasoning skill (MRS). At amount of 135 students from four public senior high school participated in the study. The study used pre-test and post-test on MRS to find the improvement of MRS and scale of perception to reveal the students perception on the SB and SW. The findings showed the students MRS improved albeit in low category and the students had positive response to either the SB or SW.